Appetitus Socialis Berolinensis - Jan Thiessen (Rechtsgeschichte - Legal History)
Business law is highly inﬂuenced by its political, social and, of course, economic surroundings. This is in particular true with respect to the socalled »Berlin Republic«, the socio-political context that emerged post-German-reuniﬁcation. After 1990, German business law, which originated from the comprehensive codiﬁcations carried out in the late 19th century, was exposed to the forces of globalization and Europeanization and the dawn of the digital age. This article examines how jurists of different professions, that is, legislators, judges, lawyers and scholars, gradually re-shaped the traditional landscape of national statutory law and case law in times of global commerce, competition and communication.